2011
DOI: 10.1128/aac.05102-11
|View full text |Cite
|
Sign up to set email alerts
|

Increased pfmdr1 Copy Number and Sequence Polymorphisms in Plasmodium falciparum Isolates from Sudanese Malaria Patients Treated with Artemether-Lumefantrine

Abstract: Molecular markers for surveillance of Plasmodium falciparum resistance to current antimalarials are sorely needed. A 28-day efficacy study of artemether-lumefantrine in eastern Sudan identified 5 treatment failures among 100 evaluable patients; 9 further individuals were parasite positive by PCR during follow-up. Polymorphisms in pfatpase6 and pfmdr1 were evaluated by DNA sequencing. One individual carried parasites with a novel pfmdr1 polymorphism (F1044L). pfmdr1 gene amplification in parasites prior to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
84
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 35 publications
8
84
2
Order By: Relevance
“…Furthermore, for SEA, it was suggested that Pfmdr1 amplification was inversely related to the 86Y mutant allele (51), but in Africa, parasites harboring multiple copies of the Pfmdr1 gene together with the 86Y mutant allele have been reported in Sudan, Gabon, and Ethiopia (46,52,53). In the present study, this association was observed at a low prevalence.…”
Section: Discussionsupporting
confidence: 43%
“…Furthermore, for SEA, it was suggested that Pfmdr1 amplification was inversely related to the 86Y mutant allele (51), but in Africa, parasites harboring multiple copies of the Pfmdr1 gene together with the 86Y mutant allele have been reported in Sudan, Gabon, and Ethiopia (46,52,53). In the present study, this association was observed at a low prevalence.…”
Section: Discussionsupporting
confidence: 43%
“…This finding suggests that the high diversity in rural areas may be due to the low drug pressure, contrasting with urban areas of Sudan where only two haplotypes have been found [42]. Interestingly, the prevalence of the NFD haplotype, strongly involved in the decrease of AL sensitivity, was one of the lower haplotypes in the study and that could indicate a small consumption of AL in Dienga.…”
Section: Discussionmentioning
confidence: 51%
“…12 The generated data from the baseline, especially the absence of the polymorphisms D1246 and N1042, which have been reported to exhibit a strong association with resistance to MQ, However, increased gene copy number not only seems to display a positive association with decreased sensitivity to MQ and artemisinin derivatives in vitro 12 but has also been indicated with artemether-lumefantrine treatment failure in subSaharan Africa. 43 Furthermore, a recent report from Nigeria linked the N86-Y184F-D1246 genotype with artemether-lumefantrine treatment failure, 44 and the N86 haplotype has been suggested as a potential marker of lumefantrine resistance in vivo, because recurrent parasites displayed a significant increase in pfmdr1 N86 after exposure to artemether-lumefantrine in Zanzibar. 45 This polymorphism has also been postulated as the first step in a series of mutation steps leading to the selection of artemether-lumefantrine resistance.…”
Section: Discussionmentioning
confidence: 99%